Saúde auditiva: estudo do grau de satisfação de usuários de aparelho de amplificação sonora - Farias, Rodrigo Brayner de (2007)
Objectives: This study aimed at characterizing the hearing aid satisfaction of adult and aged individuals derived from public hearing health care services, investigating its relationship with some variables, such as sex, age, degree of hearing loss, hearing aid type and hearing aid electro acoustic profile and comparing its result with the normative data reported by the questionnaire s authors. Method: 39 individuals were evaluated, 21 males and 18 females, aged from 19 to 90 years. All of them had conductive, sensorineural or mixed, symmetric or asymmetric, mild, moderate or severe hearing loss and used their hearing aids from not less than four weeks and not more than 12 weeks. It was used the Satisfaction with Amplification in Daily Life - SADL questionnaire Results: There was statistically significant association in the relationship between hearing aid satisfaction and hearing aid type, where in the ear hearing aid users were more satisfied than behind the ear hearing aid users. SADL global and subscale scores were higher than those described by the questionnaire s authors. Conclusions: The conclusions point out to the importance of hearing aid satisfaction evaluation to validate the effectiveness of its adaptation, contributing to get better results